The role of digitalization in the FDI – income inequality relationship in developed and developing countries - Nguyen, Van Bon (Universidad ESAN. ESAN Ediciones, 2023)
Purpose: The study aims to use individuals using the internet and fixed broadband subscriptions as a proxy for digitalization to empirically assess the effects of Foreign Direct Investment (FDI), digitalization, their interaction on income inequality in developed and developing countries from 2002 to 2019. Design/methodology/approach: The paper used the system general method of moments (GMM) estimators for 30 developed and 35 developing countries. Findings: FDI increases income inequality in developed countries but decreases it in developing countries, digitalization reduces income inequality in both groups, interaction term narrows income inequality in developed countries but widens it in developing countries. Originality/value: The paper is the first to introduce digitalization into the FDI – income inequality relationship. Furthermore, it provides empirical evidence to show the difference in the role of digitalization in this relationship between developed and developing countries.

Objetivo: El estudio tiene como objetivo utilizar a personas que utilizan Internet y suscripciones de banda ancha fija como sustituto de la digitalización para evaluar empíricamente los efectos de la inversión extranjera directa (IED), la digitalización y su interacción en la desigualdad de ingresos en los países desarrollados y en desarrollo de 2002 a 2019. Diseño/metodología/enfoque: El documento utilizó estimadores del método generalizado de los momentos (GMM) para 30 países desarrollados y 35 países en desarrollo. Hallazgos: La IED aumenta la desigualdad de ingresos en los países desarrollados pero la disminuye en los países en desarrollo, la digitalización reduce la desigualdad de ingresos en ambos grupos, el término de interacción reduce la desigualdad de ingresos en los países desarrollados pero la amplía en los países en desarrollo. Originalidad/valor: El artículo es el primero en introducir la digitalización en la relación IED-desigualdad del ingreso. Además, proporciona evidencia empírica para mostrar la diferencia en el papel de la digitalización en esta relación entre los países desarrollados y en desarrollo.
Keywords: FDI inflows; Digitalization; Entradas de IED; Income inequality; Digitalización; Developed countries; Desigualdad de ingresos; Países desarrollados; Developing countries; Países en desarrollo; https://purl.org/pe-repo/ocde/ford#5.02.04